MOTIFS OF ESCHATOLOGY IN THE EARLY PROSE OF VICTOR PELEVIN - Ayupov T. R. (Bright Mind Publishing, 2025)
The lack of research into Viktor Pelevin's work and the role of eschatological motifs and images refracted through the prism of postmodernism in his works determines the relevance of this study. Its aim is to examine the peculiarities of the embodiment of images of eschatological mythology and their selection in the process of the author's creation of novels in the 1990s.
Keywords: Postmodern novel, novels by Victor Pelevin, mythological novel, eschatological plot, eschatological novel.